1994
DOI: 10.1056/nejm199409293311303
|View full text |Cite
|
Sign up to set email alerts
|

Oral Budesonide for Active Crohn's Disease

Abstract: In an eight-week trial, an oral controlled-release preparation of budesonide at an optimal daily dose of 9 mg was well tolerated and effective against active Crohn's disease of the ileum and proximal colon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
176
0
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 514 publications
(186 citation statements)
references
References 18 publications
7
176
0
3
Order By: Relevance
“…Despite general agreement that treatment decisions for active Crohn's disease should be based on the site as well as the activity and behavior of the disease, the sample size is too small for statistically valid conclusions to be drawn from therapeutic trials when patients are stratified according to the site of disease [117] . For mildly active IBD, budesonide 9 mg/d is favored because it is superior to both placebo (OR = 2.85, 95%CI: 1.67-4.87) [118,119] and 5-ASA 4 g/d (OR = 2.8, 95%CI: 1.50-5.20) [120] , and it achieves remission in 51%-60% of individuals over 8-10 wk [119,[121][122][123] . Budesonide is preferred to prednisolone for mildly active CD because it is associated with fewer side effects, although a Cochrane systematic review has shown budesonide to be somewhat less effective than prednisolone (pooled OR for the five trials 0.69, 95%CI: 0.51-0.95) [119] .…”
Section: Filipovic Br Et Al Psychiatric Discomfort and Ibd Treatmentmentioning
confidence: 99%
“…Despite general agreement that treatment decisions for active Crohn's disease should be based on the site as well as the activity and behavior of the disease, the sample size is too small for statistically valid conclusions to be drawn from therapeutic trials when patients are stratified according to the site of disease [117] . For mildly active IBD, budesonide 9 mg/d is favored because it is superior to both placebo (OR = 2.85, 95%CI: 1.67-4.87) [118,119] and 5-ASA 4 g/d (OR = 2.8, 95%CI: 1.50-5.20) [120] , and it achieves remission in 51%-60% of individuals over 8-10 wk [119,[121][122][123] . Budesonide is preferred to prednisolone for mildly active CD because it is associated with fewer side effects, although a Cochrane systematic review has shown budesonide to be somewhat less effective than prednisolone (pooled OR for the five trials 0.69, 95%CI: 0.51-0.95) [119] .…”
Section: Filipovic Br Et Al Psychiatric Discomfort and Ibd Treatmentmentioning
confidence: 99%
“…In the cells treated with free budesonide solution, we observed an immediate decrease of Il-8 production within the first 24 h of treatment. The effect did not last long, and the release rate rebounded and increased after the second day to fourth day, which fits with the in vivo dosing scheme of free budesonide that is renewed daily (Greenberg et al, 1994). Meanwhile, the PlGA-budesonide dispersion reduced the Il-8 release levels almost to the levels of the healthy control and maintained them throughout the experimental duration of 4 days (Fig.…”
Section: Discussionmentioning
confidence: 49%
“…the encapsulated drugs then are released upon the degradation of the nanocarrier in the desired areas (tabata et al, 1996). This passive targeting to the inflamed intestinal tissue using nanocarriers was successfully applied with different kinds of drugs (e.g., tacrolimus, rolipram, and 5-ASA) and different nanocarrier technologies by showing increased therapeutic efficacy and reduced adverse effects compared to free drug molecules (lamprecht et al, 2001c;Rutgeerts et al, 2009;Greenberg et al, 1994). Formulation development and testing in these studies was conducted in different rodent models of colitis based on the chemical induction of an acute inflammation by dextran sodium sulfate (DSS) or tri-nitrobenzene sulfonic acid (tNBS) (Hasani et al, 2009;lamprecht et al, 2001b).…”
Section: Introductionmentioning
confidence: 99%
“…When given in an oral controlled ileal release (CR) formulation to patients with active ileocaecal CD, budesonide was not significantly less effective than prednisolone in inducing remission in one study [14] and substantially better than placebo in another [15] . Side-effects were much fewer in patients given budesonide CR than prednisolone, as was adrenal suppression assessed by measurement of plasma cortisol levels [14] .…”
Section: New Formulations and Applications Of Existing Drugsmentioning
confidence: 99%